Autologous Bone Marrow Mononuclear Cell Transplantation Therapy Improved Symptoms in Patients with Refractory Diabetic Sensorimotor Polyneuropathy via the Mechanisms of Paracrine and Immunomodulation: A Controlled Study. (10th August 2020) - Wei, Wei; Li, Li; Deng, Lin; Wang, Zhong-Jing; Dong, Jing-Jian; Lyu, Xiao-Yu; Jia, Ting; Wang, Li; Wang, Hong-Xiang; Mao, Hong; Zhao, Shi
We recently reported that transplantation of autologous bone marrow mononuclear cells (BM-MNCs) may be an effective and promising therapy to treat refractory diabetic sensorimotor polyneuropathy (DSPN) in patients with type 2 diabetes mellitus (T2DM). This study was designed to investigate the potential mechanisms of BM-MNCs therapy, which recruited 60 patients with DSPN, 30 T2DM patients without complications, and 30 healthy control participants. All clinical parameters, the levels of inflammatory markers, and growth factors in the three groups were compared. Patients in DSPN group had higher level of tumor necrosis factor-α (TNF-α) (DSPN vs control, 412.90 ± 64.58 vs 374.81 ± 63.18 pg/mL, P < 0.01) and lower level of vascular endothelial growth factor (VEGF) (DSPN vs control, 140.93 ± 24.78 vs 157.39 ± 25.11 pg/mL, P < 0.01) than those in control group. DSPN group had the highest level of soluble intercellular adhesion molecule-1 (sICAM-1) among three groups (DSPN and DM vs control, 1477.56 ± 228.00 and 1342.17 ± 237.54 vs 1308.00 ± 200.94 ng/mL, P < 0.05). The level of nerve growth factor in the DSPN group was slightly lower than that in the DM group (DSPN vs DM, 3509.11 ± 438.39 vs 3734.87 ± 647.50 pg/mL, P < 0.05). All patients with DSPN received one intramuscular injection of BM-MNCs and clinical follow-ups after the therapy for 2 days, 1, 4, 12, 24, and 48 weeks. Neuropathic symptoms of foot pain, numbness, and weakness were significantly improved within 4 weeks after BM-MNCs injection. Patients with DSPN were divided into the responder ( n = 35) and nonresponder groups ( n = 19) based on the improvement of nerve conduction velocity at 12 weeks post-transplantation. Compared with nonresponders, responders were younger (57.3 ± 5.2 vs 62.0 ± 4.8, P < 0.01), had a shorter history of diabetes (7.1 ± 2.7 vs 11.2 ± 5.4 years, P < 0.01), and had higher numbers of mobilized CD34 + cells (17.61 ± 2.64 vs 14.79 ± 1.62 ×10 5 /L, P < 0.01) and BM-MNCs (12.05 ± 2.16 vs 9.84 ± 1.53 ×10 8 /L, P < 0.01). The levels of TNF-α and sICAM-1 decreased just after BM-MNCs injection in both groups and slowly reverted to baseline levels. The duration of the downtrend of TNF-α and sICAM-1 in the responder group lasted longer than that in the nonresponder group. Serum level of VEGF in the responder group increased immediately after BM-MNC therapy and reached the highest point after the injection for 12 weeks. On the other hand, VEGF levels in the nonresponder group only increased slightly. Binary logistic regression was performed to evaluate the corresponding prognostic factors for BM-MNCs treatment. The number of applied CD34 + cells and the duration of diabetes were the independent predictors of responding to BM-MNCs therapy. No adverse event associated with the treatment was observed during follow-up observations. These results indicated that BM-MNCs transplantation is an effective and promising therapeutic strategy to treat refractory DSPN. The immune regulation and paracrine function of BM-MNCs may contribute to the improvement of DSPN. Trial registration: Chinese Clinical Trial Registry, ChiCTR-TRC-12002570. URL:http://www.chictr.org.cn/showproj.aspx?proj=6981